AUTOIMMUNE DISEASE, FAMILIAL CLUSTERING AND THYROID CARCINOMA COEXISTENT WITH AUTOIMMUNE THYROIDITIS IN CHILDREN AND ADOLESCENCE: A CROSS-SECTIONAL STUDY FROM THE CZECH REPUBLIC - Pomahačová, Renata; Zamboryová, Jana; Černá, Zdeňka; Sýkora, Josef; Zapletalová, Jiřina (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The prevalence of autoimmune thyroiditis (AIT), as the most common autoimmune disease (AD) and papillary thyroid cancer (PTC) is steadily rising in children. The aim of this study was to determine the coexistence of other AD and thyroid carcinoma (TC) in AIT. METHODOLOGY The cross-sectional study conducted at a tertiary center comprised AIT children (<19 years). Data on age/sex, thyroid function, ultrasound, autoantibodies, associated AD, familial occurrence of AD and the occurrence of TC for each child were collected. RESULTS In total, 231 patients (77% females) were included. The most common onset (66%) was during adolescence. At onset, hypothyroidism was detected in 59.3%; hashitoxicosis in 1.3%. The positivity of both autoantibodies was present in 60.6%, the negativity in 3,5%. We confirmed a high frequency (44.6%) of AD with AIT predominance in parents and/or grandparents of patients and in siblings (7.4%). 15.2% had at least 1 comorbid AD, of which type 1 diabetes mellitus was the most common (8.5%). Over a period of 7 years, TC was diagnosed in 16 patients (mean age 13.5 years) with predominance of PTC in 15 (94%) patients. AIT had concurrently 69% patients. 56% of patients had metastases (89% in AIT subjects). An invasive PTC was present in 44% (86% in AIT subjects). CONCLUSION The prevalence rate of AD in AIT and the first–degree relatives is high, and several new associations have been reported. Providers should be aware of comorbidities and TC in AIT as this would help early diagnoses and timely interventions.